Effect of transient scrotal hyperthermia on human sperm: an iTRAQ-based proteomic analysis - Yan-Qing Wu; Meng Rao; Shi-Fu Hu; Dan-Dan Ke; Chang-Hong Zhu; Wei Xia (BMC, 2020)
Abstract Background Through this prospective study, we aimed to explore the change of molecular modification after the transient scrotal hyperthermia on human sperm. Methods Ten healthy subjects selected with strict screening criteria underwent testicular warming in a 43 °C water bath for 30 min a day for 10 consecutive days. Semen samples were collected 2 weeks before the first heat treatment and 6 weeks after the first heat treatment. Proteins from the samples were labeled with isobaric tags for relative and absolute quantitation and analyzed by two-dimensional liquid chromatography-tandem mass spectrometry. Results In contrast to the control, of the 3446 proteins identified, 61 proteins were deregulated: 28 were up-regulated and 33 were down-regulated. Approximately 95% of the differentially expressed proteins were found to participate in spermatogenesis, fertilization, or other aspects of reproduction. In particular, the expression of sperm motility and energy metabolism-related proteins AKAP4, SPESP1, ODF1, ODF2, GAPDHS, and ACTRT2, validated by western blotting of the proteins obtained from human and mouse samples, tended to be reduced under scrotal hyperthermia. Conclusions The results indicated that the proteins AKAP4, ODF1, ODF2, GAPDHS, SPESP1, and ACTRT2, play an important role in the heat-induced reversible reduction in sperm concentration and motility and have the potential to be the biomarkers and clinical targets for scrotal heat treatment induced male infertility.